If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 2x + 2 Reorder the terms: -3 + 2x = 2x + 2 Reorder the terms: -3 + 2x = 2 + 2x Add '-2x' to each side of the equation. -3 + 2x + -2x = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 + 0 = 2 + 2x + -2x -3 = 2 + 2x + -2x Combine like terms: 2x + -2x = 0 -3 = 2 + 0 -3 = 2 Solving -3 = 2 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 5n^2-40n=0 | | g+48=54 | | 6y+6=2y+8 | | 9-4x=2x-3 | | 45/4m=35/3 | | f=53-24 | | 5k^2+20k=-15 | | ln(x)+ln(2x)=0 | | 52y-3.1=12 | | 19(v+4)-3v=4(4v+4)-24 | | 5x6/15-2 | | 2-x=2x-6 | | 3m^2-6m=9 | | 4.5(x+5.5)=4.5(x+5.5) | | 13t+10=-3 | | 5t+6=26 | | x^3=6x+x^2 | | 26+3y-3=15y-12-5y | | 5a-10=-5a | | 6v^2+252=78v | | 12y+164=7.6 | | 50t^2+80t+32= | | 0.18y+0.02(y+6000)=1120 | | 1-3/5=-1/5 | | -3(-2)+4= | | 5m^2-18M+9=0 | | -5/2t=4 | | -19(-2)= | | 6c-a/7=b | | 9m+3m-10=3(3m+3) | | 10=4k+6 | | x+20+3x=-15-3x-21 |